Exploring Cikole: What Drives Millennials to Visit and Return to Lembang Ecotourism: Jelajah Cikole: Apa yang Menggerakkan Milenial untuk Datang dan Kembali ke Ekowisata Lembang - Dewi Ratih Puspito Retno; Mauliyah Nurul Azizah; Puput Emilia Putri; Ainin Ainin Nujulah; Rifdah Abadiyah (Universitas Muhammadiyah Sidoarjo, 2026)
General Background Understanding youth tourism behavior is essential for sustainable destination management. Specific Background Cikole Lembang offers pine forest aesthetics and ethical civet coffee experiences. Knowledge Gap However, qualitative insights into how millennial push-pull motivations shape revisit intentions in ethical ecotourism remain limited. Aims This study investigates push and pull factors influencing millennial visitors and identifies key determinants of their revisit intentions. Results Qualitative thematic analysis reveals urban escape and social media content creation as dominant push factors, while pine forest aesthetics and transparent animal welfare practices serve as core pull factors. Revisit intentions are strongly driven by memorable emotional experiences and authentic peer recommendations. Novelty The findings highlight that intentional product scarcity and transparent ethics build long-term visitor loyalty without aggressive digital marketing. Implications Ecotourism managers can foster sustainable loyalty by prioritizing authentic experiences and animal welfare over promotional volume. Key Findings Highlights Escaping urban stress and generating social media content act as interconnected internal push drivers for young tourists. Transparent animal welfare standards transform initial visitor skepticism into long-term trust and destination loyalty. Strategic product scarcity and operational consistency sustain customer retention more effectively than aggressive promotions. Keywords: Revisit Intention, Push-Pull Theory, Cikole Lembang, Social Media, Animal Welfare